2022
DOI: 10.3390/cells11233740
|View full text |Cite
|
Sign up to set email alerts
|

ECM Substrates Impact RNAi Localization at Adherens Junctions of Colon Epithelial Cells

Abstract: The extracellular matrix (ECM) plays crucial roles in tissue homeostasis. Abnormalities in ECM composition are associated with pathological conditions, such as fibrosis and cancer. These ECM alterations are sensed by the epithelium and can influence its behavior through crosstalk with other mechanosensitive complexes, including the adherens junctions (AJs). We have previously shown that the AJs, through their component PLEKHA7, recruit the RNAi machinery to regulate miRNA levels and function. We have particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…These results outline a potential novel mode of interaction between AJs and ECM, through the RNAi machinery, which could influence epithelial cell behavior. Altogether, our recently published (8,93) and present findings outline a mechanosensitive RNAi machinery that interacts with the ECM to fine-tune the mechanical responses and behavior of the cell. Fully delineating this crosstalk between the AJs and the ECM through RNAi and miRNAs and understanding all the components involved, can provide new insights into tissue homeostasis and disease pathogenesis, and will be the goal of our upcoming studies.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These results outline a potential novel mode of interaction between AJs and ECM, through the RNAi machinery, which could influence epithelial cell behavior. Altogether, our recently published (8,93) and present findings outline a mechanosensitive RNAi machinery that interacts with the ECM to fine-tune the mechanical responses and behavior of the cell. Fully delineating this crosstalk between the AJs and the ECM through RNAi and miRNAs and understanding all the components involved, can provide new insights into tissue homeostasis and disease pathogenesis, and will be the goal of our upcoming studies.…”
Section: Discussionmentioning
confidence: 61%
“…Due to their actomyosin connections, AJs are known mechanosensitive complexes that respond to mechanical cues, including those that stem from the ECM (78,92). Along these lines, we have previously shown that collagen I and fibronectin negatively affect the localization and complex formation of PLEKHA7 and of the RNAi machinery at adherens junctions and throughout the cell (93). Since collagen I and fibronectin introduce an ECM that exerts stronger forces to cells, which can accordingly alter cytoskeletal dynamics (21), it is likely that the effects of these ECM components to the junctional RNAi machinery and miRNAs are mediated by the actin cytoskeleton, especially since we have shown that the latter is critical for AGO2 localization and miRNA function at AJs.…”
Section: Discussionmentioning
confidence: 97%
“…C-IV will occur in the serum when the basement membrane is formed or destroyed. 23,24 MMP-2 and MMP-9 are the members of the matrix metalloproteinase (MMPs) family. Many studies have shown that MMPs, as important enzymes currently known to degrade ECM, play an important role in promoting tumor angiogenesis, metastasis, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…, 2015 , 2017b) and to fully reconstruct their regulation and roles in cell and tissue homeostasis and disease. For example, we have recently shown that different extracellular matrix (ECM) components distinctly impact localization and complex formation of RNAi components to the ZA, including not only RISC and AGO2, but also DROSHA and the microprocessor ( Daulagala and Kourtidis, 2022 ). It is well-established that different ECM components exert different mechanical forces in cells, which are primarily transmitted through the actomyosin cytoskeleton ( Janmey et al.…”
Section: Discussionmentioning
confidence: 99%